TRAINING MANAGEMENT DEVELOPMENT PROGRAM FOR IMPROVING TEACHER QUALITY IN THE ERA OF SOCIETY 5.0 - Asmuni, Hadiqoh (UII Darullughah Waddawah Pasuruan, 2023)
Improvement efforts in the field of education are a must to always be carried out so that a nation can progress and develop along with advances in science and technology, now has entered the era of society 5.0 where humans are required to solve social problems with innovation and centered on technology. This study aims to find out how to develop appropriate management in the era of society 5.0 in order to improve the quality of teachers who are increasingly required to master technology. The preparation of this article was carried out using the library research method which consisted of determining the theme of the discussion, searching for reference sources according to the theme of the discussion, compiling the content of the material, and concluding the results from several reference articles. The theory used is the relationship between training management and teacher quality in the era of society 5.0. The results of the study indicate that education and training management in the current era must carry out reforms according to needs, education and training are packaged into activities that are able to improve mindsets, new innovations, and also mastery of technology for teachers in schools, so as to be able to create modern learning according to the needs of the times.